2666 - Bolano, Roberto 1953-2003 (Farrar, Straus and Giroux, 2008)
An American sportswriter, an elusive German novelist, and a teenage student interact in an urban community on the U.S.-Mexico border where hundreds of young factory workers have disappeared.